Pattern of Acute Abdominal Pain among Patients Attending to the Emergency Department of Karnali Academy of Health Sciences: Hospital Based Cross Sectional Study - Samal, Anup Mangal; Rawal, Mangal; Shrestha, Arun (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: Acute abdominal pain (AAP) is a medical emergency, characterized by pain arising from the abdominal area, of non-traumatic origin with a maximum duration of five days. Timely evaluation of acute abdominal pain (AAP) is important as it may determine the long-term prognosis. This study aims to assess various aspects of acute abdomen pain among patients who presented to the emergency department (ED) of Karnali Academy of Health Sciences (KAHS) in an attempt to determine the pattern and prevalence of AAP in a rural Karnali region of Nepal. Methodology: A hospital based retrospective study was conducted in KAHS. Data was collected from admission registers in ED that contained information of patients. Patients presenting to the ED during a period of six months (May 2020- October 2020) with acute abdominal pain, non-traumatic in origin were included in the study. Statistical analysis was done using SPSS version 17. Frequency and percentage were used for analysis. Result: A total of 215 patients had visited the ED with acute abdomen. Acute gastritis (48.6%) was the most common cause of acute abdominal pain in ED followed by acute appendicitis (11.6%). A total of 70 cases (32.5%) had purely surgical nature of aetiology. Acute abdominal pain was seen equally distributed between both genders. Patients of AAP mostly belonged to the middle age group (44.6% in an age group of 15-30 years). Conclusion: Most cases of Acute Abdominal Pain (AAP) attending the emergency department of a hospital in the mountainous region of Karnali have conditions relating to non-surgical cause. While acid peptic disease remains a common entity among people living in rural Karnali region of Nepal, further elaborative study of AAP is recommended